Implementation of a video-messaging service in the neonatal intensive care unit: A literature review - Setiyawati, Atik (Holistik Jurnal Kesehatan, 2023)
Background: The NICU room is a critical area for newborns where various problems, such as anxiety and bonding parents with their babies, limited workforce, communication and education difficulties. Video service technology can be a solution to these problems.Purpose: Know the effectiveness of using video services in NICU nursing.Method: The form of a literatur review. database searches are carried out through ProQuest, Scopus, Science Direct, Ebsco and PubMed since 2018-2023.Result: From the results of a review of 10 journals, video service provides positive benefits for patients' parents, NICU professionals, and nurses. Video service can be a bridge of communication between parents and babies, parents and health workers, and increase nurses' job satisfaction.Conclusion: Further studies are needed to examine more deeply the benefits of video service for nurses in the NICU room.Keywords: Live Video Service; Neonatal Care; ParentPendahuluan: Ruang NICU merupakan area kritis bayi baru lahir dimana berbagai permasalahan, seperti kecemasan dan bonding orangtua dengan bayinya, kesibukan tenaga kerja yang terbatas, kesulitan komunikasi dan edukasi. Teknologi video service dapat menjadi solusi untuk permasalahan tersebut.Tujuan: Mengetahui efektivitas penggunaan video service dalam keperawatan NICU.Metode: Metode yang digunakan dalam penelitian ini adalah literature review. Penelusuran artikel akademik melalui Online Database pencarian melalui Online Database diantaranya ProQuest, Scopus, Science Direct, Ebsco dan PubMed dari tahun 2018-2023.Hasil: Dari hasil telaah 10 jurnal, video service memberikan manfaat positif bagi orang tua pasien, profesional di ruang NICU, dan perawat. Video service dapat menjadi jembatan komunikasi antara orangtua dan bayi, orang tua dan petugas kesehatan, serta meningkatkan kepuasan kerja perawat.Simpulan: Studi lanjutan diperlukan untuk mengkaji lebih dalam manfaat video service untuk perawat di ruang NICU.